Effect of vernalization period and bulb size on bolting of onion cultivar “Texas Early Grano” grown under Gezira conditions, Sudan - Elsiddig, Elfatih A.M; Elamin, Osman M (Gezira Journal of Agricultural Science; Vol 12 No 1 (2014), 2014)
Texas Early Grano onion cultivar is very popular in Sudan and is used mainly as a salad vegetable. Unfortunately, this cultivar does not flower and produce seeds under Sudan conditions and seeds should be imported from abroad. Attempts to produce seeds of this cultivar under Gezira conditions have failed. Therefore, the objective of this research was to study the effects of bulb size and vernalization on the induction of flowering of Texas Early Grano onion cultivar. Experiments were conducted at the research farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during the  winter seasons of 2008/09 and 2009/10.   Treatments consisted of vernalization periods ranging from 45 to 180 days, storage temperatures of 4 to 5 0 C, and bulb size which was small and medium. Treatments were arranged in a  randomized complete block design with three replicates. Results indicated that vernalization duration significantly affected emergence percentage. As vernalization duration increased, emergence percentage increased in both seasons. Bulb size had no significant effects on emergence percentage. Vernalization temperatures of 4 to 5 0 C for 90 days or more was the key factor for the induction of bolting of Texas Early Grano cultivar. To obtain the highest bolting percentage and seed yield, a combination of venrnalization at 4 to 5 0 C for 180 days and medium-sized bulbs should be recommended.       يعتبر صنف البصل "تكساس إيرلى جرانو" من الأصناف المعروفة في السودان التي تستخدم كأحد الخضر الرئيسية في طبق السلطة. محاولة إنتاج بذور هذا الصنف محلياً لم تعط نتائج إيجابية نسبة لعدم توفر درجات الحرارة المنخفضة اللازمة لتحفيز الإزهار تحت ظروف ولاية الجزيرة. لذا هدفت هذه الدراسة إلى تحفيز الإزهار لإنتاج البذور من هذا الصنف باستخدام ظاهرة الإرتباع (التخزين المبرد) لأحجام مختلفة من الأبصال. أجريت هذه الدراسة بمزرعة كلية العلوم الزراعية، جامعة الجزيرة، واد مدني، السودان خلال موسمي 2008/09 و 2009/10م. شملت التجارب فترات تخزين مبرد تراوحت ما بين 45- 180 يوما في درجات حرارة تراوحت ما بين 4 إلي 5 0 م ونوعين من حجم الأبصال (صغير ومتوسط).  استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات. أشارت النتائج إلى أن التخزين المبرد في درجات الحرارة 4 - 5°م هو العامل الرئيسي المحفز للإزهار في صنف البصل "تكساس إيرلي جرانو". التخزين المبرد أظهر تاثيراً معنوياً في نسبة الانبات، فكلما زادت فترة التخزين المبرد زادت نسبة الانبات في كلا الموسمين، بينما لم يؤثر حجم الأبصال في نسبة الانبات. تم الحصول على أعلى نسبة للإزهار وإنتاجية البذور بزراعة الأبصال متوسطة الحجم والمخزنة في درجة حرارة 4 - 5°م لفترة 180 يوما. لذلك يوصى بتخزين الأبصال متوسطة الحجم في درجات حرارة تتراوح بين 4 - 5°م لفترة 180 يوما أو اكثر للحصول على بذور صنف البصل "تكساس إيرلي جرانو" تحت ظروف ولاية الجزيرة.